FAKTOR YANG MEMPENGARUHI PEMAHAMAN PELAKU UMKM DALAM MENYUSUN LAPORAN KEUANGAN - Irawan, Azhar Ayu Tri; Khomsatun, Siti (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2025)
This study aims to analyse the influence on the understanding of MSME actors in preparing financial statements based on SAK EMKM. The research employed a quantitative approach, with the understanding of MSME actors in preparing financial reports as the dependent variable. The sample consisted of MSME actors conducting business activities through e-commerce or marketplace platforms and residing in Bekasi. A total of 40 respondents participated in the study. The findings reveal that educational background, access to information and socialisation statistically significantly influence the understanding of MSME actors in preparing financial statements based on SAK EMKM. Conversely, educational level and business age do not significantly impact. These results imply that MSME actors with an accounting background tend to have better bookkeeping practices due to their familiarity with accounting processes and SAK EMKM. Keywords: Age of Business, Education Background, Education Level, Information and Socialisation, Understanding of MSME actors in preparing financial statements